2020
DOI: 10.1177/0898264320929537
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Needs and Service Utilization in Older U.S. Adults Evidencing High-Risk Substance Use

Abstract: Objectives: Because substance misuse by older adults poses clinical risks and has not been recently assessed, we examined substance use patterns, treatment needs, and service utilization in those evidencing high-risk use. Methods: We identified National Survey on Drug Use and Health respondents (2015–2018) aged ≥50 years reporting multiple-occasion binge drinking, illicit drug use, prescription drug misuse, or substance dependence. Past-year psychological symptoms were assessed using validated scales. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…These low rates of treatment have been observed in previous research, especially in persons with substance use disorder, and may be due to stigma; treatment access or cost challenges; the desire to continue using substances of abuse; a perception that treatment is unnecessary; and, among older adults, lack of age-appropriate treatment venues for persons with mobility or sensory impairments. 51 -54 Our findings are also consistent with national survey data on veterans of the wars in Afghanistan and Iraq, suggesting gaps between knowledge of heart disease risk factors and engagement in preventive activities, such as stress reduction or healthy blood pressure maintenance. 55…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These low rates of treatment have been observed in previous research, especially in persons with substance use disorder, and may be due to stigma; treatment access or cost challenges; the desire to continue using substances of abuse; a perception that treatment is unnecessary; and, among older adults, lack of age-appropriate treatment venues for persons with mobility or sensory impairments. 51 -54 Our findings are also consistent with national survey data on veterans of the wars in Afghanistan and Iraq, suggesting gaps between knowledge of heart disease risk factors and engagement in preventive activities, such as stress reduction or healthy blood pressure maintenance. 55…”
Section: Discussionsupporting
confidence: 83%
“…continue using substances of abuse; a perception that treatment is unnecessary; and, among older adults, lack of ageappropriate treatment venues for persons with mobility or sensory impairments. [51][52][53][54] Our findings are also consistent with national survey data on veterans of the wars in Afghanistan and Iraq, suggesting gaps between knowledge of heart disease risk factors and engagement in preventive activities, such as stress reduction or healthy blood pressure maintenance. 55 Coupled with that body of work, our findings highlight the potential value of querying adults regarding psychological symptoms and substance use behaviors in routine health care encounters, consistent with the recommendations of the US Preventive Services Task Force.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, there appears to be a stigma associated with substance misuse and that treatment is not necessary for older adults. 16 Barriers associated with patients and providers have been identified in prior studies including the discomfort of screening patients and the patient’s feeling of shame surrounding substance use. 16 18 As the findings of this study have shown older adults with chronic disease have a significant association with substance misuse, attention is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, older adults are more likely to use multiple medications that may interact with alcohol or drugs, and they experience declines in liver function and reductions in the ratio of body water to fat tissue, which leads to increased blood alcohol concentration (Barry & Blow, 2016;Moore et al, 2007). Evidence of increased psychological distress and suicide risk among older adults using substances (Fairman & Early, 2020) underscores that substance use screenings should not be overlooked in this population. Efforts to reduce the stigma surrounding substance use and SUD treatment and the integration of substance use and mental health would increase treatment access among older adults and decrease psychological and physiological risks associated with substance use in this group.…”
Section: Prevalence Of Substance Use Disordersmentioning
confidence: 99%